Advancements in Camel Milk Drying Technology: A Comprehensive Review of Methods, Chemical Composition, and Nutritional Preservation - Ayaulym Rakhmatulina; Fatima Dikhanbayeva; Dinara Tlevlessova; Jelena Zagorska; Nurbek Aralbayev; Kristine Majore; Aidana Yessenova (Dairy)
With interest in camel milk growing due to its nutrients and biologically active compounds, research into methods of processing and drying it is crucial. In recent decades, extensive studies have explored its chemical composition and health benefits with a focus on drying techniques and their effects on its properties. This review systematically summarizes the available literature on camel milk drying processes and their effects on its chemical composition with a view to shortening the drying time. To achieve this goal, we meticulously reviewed numerous studies published between 2014 and 2024 to identify optimal drying methods that maximize the preservation of camel milk’s nutrient components and bioactive compounds. Our analysis revealed significant findings: freeze drying preserves nutrients better than spray drying, but is less efficient. Spray drying, while faster, tends to compromise some nutritional values. Conclusively, optimizing drying parameters can improve production efficiency and nutrient retention.